2018
DOI: 10.20944/preprints201805.0367.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Livelihoods on the Edge without a Safety Net: the Case of Smallholder Crop Farming in North-Central Namibia

Abstract: Semi-arid Namibia is marginal for agricultural production. Low soil fertility combined with low and variable rainfall restrict the livelihoods of smallholder farmers who often struggle to produce enough food. Although historically communities have adopted a number of coping mechanisms, climate change threatens to further reduce agricultural production. There are many additional options available to smallholder farmers to adapt to climate change, but they are not necessarily adopting these measures despite havi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The main climate changes perceived by pastoralists in Kunene include limited rainfall, recurrent droughts and floods. Other studies in several parts of Africa [ 35 , 63 65 ] also found similar results. In pastoral production systems, climate change and variability may manifest as flood and drought events [ 66 ].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The main climate changes perceived by pastoralists in Kunene include limited rainfall, recurrent droughts and floods. Other studies in several parts of Africa [ 35 , 63 65 ] also found similar results. In pastoral production systems, climate change and variability may manifest as flood and drought events [ 66 ].…”
Section: Discussionsupporting
confidence: 79%
“…So, the use of local knowledge to predict rain is still very useful to many in the community. However, many studies [ 32 , 35 , 63 , 71 ] have shown that traditional forecasting has become unreliable because of increasing climatic uncertainties and presented new challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations